Disclosing sexual violence in a digital society: storytelling, activism, and justice - O'Neill, Tully (Crime and justice in digital society, 2024)
This book examines the various ways that victim-survivors disclose sexual violence in digital settings and theorizes the extent to which these practices constitute a new and informal 'justice' occurring in digital space. It features qualitative research interviews conducted with victim-survivors who disclosed sexual violence online and analyzes digital spaces utilized by survivors for the purposes of support, healing, and connection. The volume provides insight into how and why victim-survivors use digital technologies to pursue ‘justice’ and the decision-making processes they undertake in order to navigate digital space after sexual violence. It expands on the theorization of informal justice in digital society and its potential implications. It focuses particularly on the experiences of justice for victim-survivors in the aftermath of sexual violence, highlighting the complexities of disclosing rape, sexual assault, and abuse in digital space.